2021
DOI: 10.2196/22844
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Changes in Depression, Anxiety, and Social Anxiety Using Smartphone Sensor Features: Longitudinal Cohort Study

Abstract: Background The assessment of behaviors related to mental health typically relies on self-report data. Networked sensors embedded in smartphones can measure some behaviors objectively and continuously, with no ongoing effort. Objective This study aims to evaluate whether changes in phone sensor–derived behavioral features were associated with subsequent changes in mental health symptoms. Methods This longitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 48 publications
3
88
1
Order By: Relevance
“…The differences in populations and applied methods could be potential reasons for the slightly inconsistent results. Both our study and that study [ 22 ] have shown that the changes in mobility prior to changes in depressive symptom severity can be captured by mobile phones. An interesting finding is that the number of residential locations was positively correlated (φ4=0.05, P =.02) with the subsequent PHQ-8 score ( Table 3 ), which is opposite to their negative correlation (ρ=−0.09, P =.001) at the within-individual level ( Table 2 ).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The differences in populations and applied methods could be potential reasons for the slightly inconsistent results. Both our study and that study [ 22 ] have shown that the changes in mobility prior to changes in depressive symptom severity can be captured by mobile phones. An interesting finding is that the number of residential locations was positively correlated (φ4=0.05, P =.02) with the subsequent PHQ-8 score ( Table 3 ), which is opposite to their negative correlation (ρ=−0.09, P =.001) at the within-individual level ( Table 2 ).…”
Section: Discussionmentioning
confidence: 72%
“…In recent years, there have been several studies [ 12 - 22 ] exploring the associations between depressive symptom severity and mobility features extracted from phone-collected location data that have shown that mobility measured by phones is negatively associated with the severity of depressive symptoms which is consistent with past survey-based studies; however, not many have explored the direction of the relationships between depression and mobility over time. Meyerhoff et al [ 22 ] recently found that phone-derived mobility features were correlated with subsequent changes in depression, but not vice versa. However, the autoregressive nature of depressive states and mobility levels [ 23 - 25 ] and the influence of individual differences may affect the results.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Using an elastic net model, which is a penalised regression model that uses both L1 and L2 loss, and 34 features from the data, the authors obtained an area under the curve (AUC) of 0.656 for predicting mood. In another large study of 288 participants studying mood and anxiety, Meyerhoff et al 6 employed a different approach, looking at correlations between changes in weekly survey scores and changes in passive data features. Focusing on GPS, call, text and app usage features, this study also reported low correlations similar to Nickels et al 5 Meyerhoff et al also separated participants into groups, using k -means clustering on the participants’ clinical scores, and found that some correlations were higher in groups exhibiting symptoms.…”
mentioning
confidence: 99%
“…Focusing on GPS, call, text and app usage features, this study also reported low correlations similar to Nickels et al 5 Meyerhoff et al also separated participants into groups, using k -means clustering on the participants’ clinical scores, and found that some correlations were higher in groups exhibiting symptoms. 6 In this work, we aim to explore correlations in a large data-set collected with the mindLAMP app from college student participants, to assess if we observe correlations of a similar magnitude to Nickels et al 5 and Meyerhoff et al 6 In addition, we explore whether changing the group of participants that we use for analysis (such as by setting data-quality thresholds or by splitting into clinical groups) will allow us to identify more clinically meaningful correlations. Finally, we aim to test a classifier for predicting survey scores with passive and survey data, to assess whether passive data signals alone are enough to build predictive models or if survey data is necessary to provide a stronger signal.…”
mentioning
confidence: 99%